STRATEGI PENGUATAN KOMPETENSI DIGITAL GURU UNTUK MENINGKATKAN INOVASI PEMBELAJARAN DI SMA AISYIYAH BOARDING SCHOOL BANDUNG - Syifa Fauziyah; Aini Insani Dangiangsari; Dewi Setiawati; Waska Warta (STKIP Pesisir Selatan, 2026)
Objective: The development of information technology demands a transformation of educators' roles in navigating the digital ecosystem within the classroom. However, studies examining the strengthening of digital competence through a managerial strategy lens remain scarce, even though a well-matured strategy is essential to enhance teachers' digital competence and subsequently drive instructional innovation. This study utilized a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, observations, and documentary studies. Data analysis employed Fred R. David's Strategic Management framework, which includes strategy formulation, strategy implementation, and strategy evaluation. The results indicated that strategy formulation was carried out through mapping teachers' digital competencies, identifying school needs, involving teachers in decision-making, and integrating digitalization programs into school planning documents. Strategy implementation was realized through In-House Training (IHT), Focus Group Discussions (FGD), external training, coaching, teacher learning communities, and the provision of supporting facilities for digital learning. Strategy evaluation was conducted continuously through academic supervision, evaluation forums, feedback provision, and follow-up measures in the form of mentoring and advanced training.